Bile canaliculi formation by aligning rat primary hepatocytes in a microfluidic device - Nakao, Yosuke (American Institute of Physics, 2011)
In this study, we propose a microfluidic cell culture device mimicking the microscopic structure in liver tissue called hepatic cords. The cell culture area of the device was designed to align hepatocytes in two lines in a similar way to hepatic cords. Thanks to the structural design together with a cell seeding procedure, rat primary hepatocytes were successfully aligned in two lines and cultured under perfusion condition. It is shown that aligned hepatocytes gradually self-organize and form bile canaliculi along the hepatic cord-like structure. The present technique to culture hepatocytes with functional bile canaliculi could be used as an alternative to animal testing in the field of drug discovery and toxicological studies, and also be beneficial to tissue engineering applications.